Long-term outcomes of living-related kidney donation for alport syndrome spectrum: a propensity score-matched analysis - VELİOĞLU, ARZU (My University, 2022)
Introduction: Data to guide the evaluation of living-related donor candidates for kidney transplant recipients with Alport syndrome (AS) spectrum are limited. We aimed to examine a cohort of living-related donors to recipients with AS and compare their outcomes with a control group to improve understanding of the clinical course and outcomes of living donation in this context. Methods: Living donors (LDs) of AS recipients and propensity score-matched control LDs without any family history of AS (control group) were followed for major cardiac events, death, post-donation estimated glomerular filtration rate (eGFR), and proteinuria. Results: There were 31 LDs (48.4% male), in whom relationship to AS recipient included mother (45.2%), father (32.3%), sibling (16.1%), grandparent (3.2%), and uncle (3.2%). Long-term outcomes over 10.0 (IQR, 3.0-15.0) years were evaluated in 25 and 25 LDs from study and control groups, respectively. During follow-up, 5 LDs (20.0%) in study group developed major cardiac event (acute coronary ischemia [n = 4] and severe congestive heart failure [n = 1]) after 5.5 (IQR, 4.5-10.3) years, whereas only 2 (8.0%) LDs in control group developed major cardiac events (p = 0.221). New-onset hypertension was higher in study group (56.0%) compared to the control group (16.0%) (p = 0.003). Three donors in study and 2 donors in control group who developed new-onset hypertension died during follow-up (p = 0.297). Major cardiac event rate was significantly higher in donors who developed hypertension after donation (0 vs. 28.0%, p < 0.001). There were no differences between study groups regarding last eGFR and proteinuria levels (p = 0.558 and p = 0.120, respectively). Discussion/Conclusion: Although the risk of kidney disease can be minimized by careful donor evaluation, our findings suggest that hypertension risk after the donation is higher than expected in related donors of recipients with AS.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Health Sciences; ÜROLOJİ VE NEFROLOJİ; Klinik Tıp; Klinik Tıp (MED); UROLOGY & NEPHROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Üroloji; Urology; Alport syndrome; Cardiovascular outcomes; Collagen; Genetics; Kidney transplantation; Living donors; JOINT CONSENSUS RECOMMENDATION; RENAL-TRANSPLANT; MEDICAL GENETICS; AMERICAN-COLLEGE; GUIDELINES; STANDARDS; VARIANTS; GENOTYPE; GENOMICS; RAMIPRIL